9+3/4x-2/3x=11

Simple and best practice solution for 9+3/4x-2/3x=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+3/4x-2/3x=11 equation:



9+3/4x-2/3x=11
We move all terms to the left:
9+3/4x-2/3x-(11)=0
Domain of the equation: 4x!=0
x!=0/4
x!=0
x∈R
Domain of the equation: 3x!=0
x!=0/3
x!=0
x∈R
We add all the numbers together, and all the variables
3/4x-2/3x-2=0
We calculate fractions
9x/12x^2+(-8x)/12x^2-2=0
We multiply all the terms by the denominator
9x+(-8x)-2*12x^2=0
Wy multiply elements
-24x^2+9x+(-8x)=0
We get rid of parentheses
-24x^2+9x-8x=0
We add all the numbers together, and all the variables
-24x^2+x=0
a = -24; b = 1; c = 0;
Δ = b2-4ac
Δ = 12-4·(-24)·0
Δ = 1
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1}=1$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(1)-1}{2*-24}=\frac{-2}{-48} =1/24 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(1)+1}{2*-24}=\frac{0}{-48} =0 $

See similar equations:

| s(0.5)=112+96(0.5)-16(0.5)^2 | | 720=460+(x+10)+x | | x=0.55555 | | 10y-7-2y=33 | | 5.8q-4.1-5.2q=-0.4q-2.4 | | X-(4x-7)=28 | | X-(4x-7)=24 | | 6z=3z+2(7+5z) | | 1.8q-3.6-5.7=-4.9q-2.7 | | 7+3x-12x=3x+11 | | 7y-3=19y+9 | | -v+217=269 | | -(n+5)=-(5-2n)+6n | | -x+63=3x+31 | | 247=190-y | | 30+9x=120 | | 5(6-a)=26 | | 12x-1+4x+10=120 | | 6(6-a)=26 | | 9y+8=13y | | 64=32+48t-15t^2 | | ×+r+1=0 | | 4b-4=-4+46 | | 12g+6=12g+18 | | x+12=5x+40 | | -r3+10=15r-8 | | 5/6=1/3+x | | 3x+20=15x | | 6y-17=-3 | | -0.13p-0.06(3-4p)=6(p-4)-0.14 | | 192=96+80t-16t^2 | | A=1.885x-3771 |

Equations solver categories